La estimulación temprana para el desarrollo de la motricidad gruesa en los niños de inicial 1 de la escuela de Educación Básica Benjamín Franklin "Science School", de la ciudad de Riobamba. - Boada Puma, Adriana Nicole (2024)
The present research is entitled "Early Stimulation for the Development of Gross motor skills in Children of Initial 1 of the Benjamin Franklin Basie Education Science School, in Riobamba City. The objective was to identify the problem and find a potential solution to the following question: How do early stimulation activities contribute significantly to the development of gross motor skills in children of initial 1 of the Benjamin Franklin Basie Education Science School in Riobamba City? Therefore, a general objective was proposed together with several specific objectives, and a theoretical framework was elaborated to support this analysis. Besides, a non-experimental and descriptive study was carried out based mainly on the review of literature and documents; this allowed us to examine the importance of early stimulation in the development of grass motor skills in the children of initial 1 of the Benjamin Franklin School of Basie Education. We worked with a representative population sample and used the observation technique, creating a card that collected information for its subsequent tabulation, analysis, and interpretation. Likewise, this approach allowed us to reach conclusions and offer recommendations. Among the achievements obtained, it highlights that applying early stimulation activities is favorable for better motor development in children.